Formulation and Evaluation of Transdermal Patch from Extract of Babadotan Leaves - Makanoneng, Dawna Stacey Derose; Suwitono, Marvel Reuben; Sulastri, Titin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Transdermal Drug Delivery System (TDDS) represents a modality for conveying therapeutic agents across the cutaneous barrieroffering an alternative route to overcome the limitations of oral formulations. This experimental investigation endeavored to formulate and assess a percutaneous patch containing Ageratum conyzoides L. leaf extract, known for its antibacterial and anti-inflammatory properties. The extract was formulated using HPMC polymer and evaluated through organoleptic tests, pH, thickness, weight uniformity, moisture absorption, and folding endurance. The results showed that the patch was a a membranous disk exhibiting a 5 cm caliber, green in color, with a characteristic herbal odor, smooth, flexible, and non-sticky surface. The hydrogen ion concentration spanned from 6.2 to 6.93, accompanied by a caliper between 0.53–0.57 mm. The patch demonstrated good folding endurance (>200 folds) and moisture content ranging from 17% to 23%. The formulation exhibited good physical stability and met the quality criteria for transdermal preparations. This patch has potential as an effective topical therapy derived from natural ingredients for treating skin infections and inflammation, and supports the utilization of local medicinal plants in the innovation of modern pharmaceutical drug delivery systems.